Heading exposure in elite football (soccer): A study in adolescent, young adult, and adult male and female players - Langdon, S.; Goedhart, E.; Oosterlaan, J., Königs, M. (Medicine & Science in Sports & Exercise, 2022)
Purpose This study aims to quantify heading exposure in real-life elite football at the level of individual male and female adolescents, young adults, and adults.